Audience reactions to the program notes of unfamiliar music. (July 2018) - Bennett, Dawn; Ginsborg, Jane
Many classical music listeners attend concerts with some knowledge of the music to be performed, especially when the repertoire is familiar and comes from the Western music canon. In the case of music that is new to the listener and/or sung in an unfamiliar language, program notes may provide essential information; however, there is little understanding of what information should be provided or the impact of this information on the listener. This article presents the findings of practice-led research that sought to determine the types and modes of information that might enhance the experiences of both listeners and performers. Listeners ( n = 29) attended a performance of unfamiliar music. The music was performed twice, with program notes shared only after the first performance. All respondents listened differently to the music once they had been given the program notes. Only 39% of listeners reported that the program notes had had a positive impact on their listening experience. More experienced listeners were far more likely to reject the program note information in favour of their own interpretation particularly if they had experiences of music-making.